2010
DOI: 10.1093/humrep/deq297
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acrosome and nuclear abnormalities in human spermatozoa with large vacuoles

Abstract: Sperm vacuoles were exclusively nuclear. In our selected teratozoospermic population, aneuploidy and chromatin condensation defects were the main alterations observed in SLV. Based on results from this small sample of spermatozoa, we propose a global impairment of the spermatogenesis process as a common origin of the morphological alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
143
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(165 citation statements)
references
References 46 publications
8
143
0
8
Order By: Relevance
“…The most predictive factor of sperm quality is the incidence of vacuoles in the sperm head [37]. The MSOME enables the selection of motile spermatozoa with fine nuclear morphology and free of head vacuoles in real time at high magnification, which are then injected into oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most predictive factor of sperm quality is the incidence of vacuoles in the sperm head [37]. The MSOME enables the selection of motile spermatozoa with fine nuclear morphology and free of head vacuoles in real time at high magnification, which are then injected into oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Perdrix et al [37] demonstrated that sperm vacuoles are exclusively nuclear. The study showed that aneuploidy and chromatin condensation defects were the main alterations observed in spermatozoa presenting large vacuoles.…”
Section: Discussionmentioning
confidence: 99%
“…In the first prospective randomized trial [14], the clinical benefit was more significant in patients with two or more previous failed treatment attempts: IMSI resulted in significantly higher clinical pregnancy rates (29.9 vs 12.9 %; P < 0.05). If large vacuoles are linked to chromatin condensation defects, as has been demonstrated by many authors [6,7,15], more rigorous selection of the sperm cell (as few vacuoles as possible) could improve the quality of the sperm injected into the oocyte. In a previous randomized controlled trial, we reported that IMSI yielded no benefit during the first assisted reproductive technique (ART) attempt.…”
Section: Introductionmentioning
confidence: 94%
“…This technique revealed a new morphological criterion in human spermatozoa: the presence of nuclear vacuoles. Several studies have found increased levels of fragmented DNA in spermatozoa with large vacuoles [2][3][4][5], whereas others [6,7] have shown abnormalities of chromatin condensation in such spermatozoa. Although the origin of these vacuoles raises many questions, some strong correlations have been established between the morphology of the spermatozoon, in particular the presence of large vacuoles, and its nuclear quality (degree of chromatin condensation and/or DNA integrity, chromosomal content) [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to the growing body of literature, it is more and more obvious that large vacuoles are a sign of nuclear dysfunction, reflecting a failure of chromatin condensation and packaging [20][21][22][23][24][25][26][27]. It has been reported that the negative impact of large nuclear vacuoles (LNV) is perceptible after the onset of the EGA, leading to reduced blastocyst formation [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%